Evaluation of buprenorphine hydrochloride Pluronic(®) gel formulation in male C57BL/6NCrl mice - Blankenship-Paris, Terry L. (Lab Anim (NY), 2016)
Providing adequate analgesia while minimizing handling and stress post-surgery can be challenging. Recently, there have been commercial products made available for providing long acting analgesia in rodents. However, we find there are limitations for use in mice due to the viscosity of the product and the small dosing volumes needed. This project evaluated an in-house compounded formulation of buprenorphine easily made in the laboratory using pharmaceutical grade products. The release of buprenorphine was evaluated when compounded with two types of hydrogels (Pluronic(®) F-127 and F-68). Mice given buprenorphine in hydrogel (BP) demonstrated higher serum levels of buprenorphine for a longer period of time compared to mice given standard buprenorphine (Bup). However, the rate of decline in serum levels between the groups was similar; thus, it is more likely that the higher buprenorphine concentration seen in the BP group is due to the higher dose of buprenorphine given, rather than a slower release of product. Feed consumption was decreased in both groups one day after dosing; however, there was no difference in body weights. Increased activity in the open field was observed with both buprenorphine formulations, and lipemia was observed in mice given BP which persisted to at least 96 h. Based on our results, we conclude that this formulation did not sustain the release of buprenorphine or eliminate the increased activity commonly seen in mice given buprenorphine. In addition, the lipemia may confound research parameters, especially in cardiac studies and lipid metabolism studies. Therefore, we cannot recommend this formulation for use.